Proposal for improving a Master’s Program in production engineering using QFD – within the context of an institutional evaluation. - Moraes, Clayton Cardoso de; Miguel, Paulo Augusto Cauchick (Revista Gestão da Produção Operações e Sistemas, 2007)
The present work discusses quality in higher education, stressing the role of self-assessment as an alternative for diagnostic of the internal situation of a higher education institution. However, the self-assessment is only a mean in the search for continuous improvement, thus, it is necessary other techniques to be combined to this process. In this sense it is presented the application of the Quality Function Deployment (QFD) in a master degree in industrial engineering. QFD was adopted to enable the development of a quality planning for services offered by the studied course. The work also considers a case study in the course and describes QFD application, followed by a quality plan. The paper concludes that, when translating students’needs concerning the services offered by the course, QFD pointed out some items, which were considered more important to obtain a positive result aligned to their necessities aiming at assuring quality in the studied course. Keywords: QFD, Higher Education, Self-assessment.